Environmental Impact 2012
DOI: 10.2495/eid120211
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of climate change on Nigerian maize sector: a Ricardian analysis

Abstract: This paper evaluates the economic impact of climate change on Nigeria's maize sector using a Ricardian approach. Data was collected on temperature, precipitation, soil, maize revenue, socioeconomic characteristics and adaptation strategies to varying climate factors. The study reveals that net maize revenue per hectare is sensitive to climate change. The impact of predicted climate scenarios from three models (CGM2, HADCM3 and PCM) indicated that there would be an increasing reduction in maize net revenue per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…When the average precipitation increases by 1 percent, the groundnuts' farm returns increase by 0.115 percent. In the same vein of research, Granados et al (2017) and Ater & Aye (2012) obtain similar results. On the contrary, average, precipitation has a significant negative relationship with farm returns for beans.…”
Section: Regressionssupporting
confidence: 54%
See 1 more Smart Citation
“…When the average precipitation increases by 1 percent, the groundnuts' farm returns increase by 0.115 percent. In the same vein of research, Granados et al (2017) and Ater & Aye (2012) obtain similar results. On the contrary, average, precipitation has a significant negative relationship with farm returns for beans.…”
Section: Regressionssupporting
confidence: 54%
“…These empirical results are consistent with those of Tokunaga et al (2015) in Japan whose elasticities are between -0.39 percent and -0.82 percent. Etwire et al (2019) in Ghana find that for 1 percent increase in average temperature, the plantains revenues decrease by 2.612 percent, in Nigeria, Ater & Aye (2012) empirically estimate elasticity as -2.589 percent. Exenberger et al (2014) find different elasticities for grouped countries, for example -0.004 percent for high income, -0.014 percent for middle income and -0.016 percent for low income.…”
Section: Regressionsmentioning
confidence: 96%
“…Moreover, impacts of climate change will vary according to location, soil type, crop, and other local factors. Consequently, it is essential to conduct enterprise-specific analysis (Ater and Aye 2012;Sarker et al 2012). In a review by Knox et al (2012), it was indicated that for yams, there were too few studies to comment on if there has been any significant impact of climate change on the yield in West Africa.…”
Section: Theoretical Overview and Evaluation Of The Climate Change Vamentioning
confidence: 99%
“…A growing body of economic literature has focused on the impacts of climate change on the agriculture sector at a macro level [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The common finding of these studies is that climatic changes adversely affect crop yields.…”
Section: Introductionmentioning
confidence: 99%